Building construction handbook - Chudley, R.; Greeno, Roger (London ; Oxford Butterworth, 2010)
"Ideal for students on all construction courses - Topics presented concisely in plain language and with clear drawings - Fully updated to include all revisions to Building and Construction regulations Building Construction Handbook is an authoritative reference for all construction students and professionals. It is full of detailed drawings that clearly illustrate the construction of building elements. The principles and processes of construction are explained with the concepts of design included where appropriate. Extensive coverage of building construction practice and techniques, representing both traditional procedures and modern developments, are also included to provide the most comprehensive and easy to understand guide to building construction. This new edition has been updated to reflect the 2011 changes to the building regulations, as well as new material on energy performance, and substantial revisions of the section on structures. Building Construction Handbook is the essential, easy-to-use resource for undergraduate and vocational students on a wide range of courses including NVQ and BTEC National, through to Higher National Certificate and Diploma, to Foundation and three-year Degree level. It is also a useful practical reference for building designers, contractors and others engaged in the construction industry"--
Includes index.
Keywords: Building -- Handbooks, manuals, etc; Construction industry -- Handbooks, manuals, etc